Associations among Religious Coping, Daily Hassles, and Resilience. (January 2013) - McIntire, Laura; Duncan, Renae
The purpose of this study is to examine relationships among religious coping styles, the experience of daily hassles, and resiliency. Through the use of a set of questionnaires, positive and negative religious coping styles (Brief RCOPE) are identified and analyzed in relation to a direct measure of resiliency (CD-RISC), level of psychological distress (BSI), and level of daily hassles (BCSHS). Negative religious coping is positively related to psychological distress, while individuals who experience more daily hassles but use higher levels of positive religious coping have greater resiliency than individuals who use higher levels of negative religious coping. Additionally, the combination of daily hassles, major life stressors, level of positive religious coping, and resiliency accounted for a significant proportion of the variability in psychological distress. Post hoc analyses removed questions of spirituality from the resiliency scale that could possibly overlap with the measure of religious coping. These exploratory analyses indicate that negative religious coping is negatively correlated with non-spiritual resiliency. Exploratory analyses also indicate that individuals who experience more daily hassles but use higher levels of positive religious coping do not have greater levels of non-spiritual resiliency than individuals who use negative religious coping.